Examining Lecturers’ Insights: Resolving Challenges and Implementing Strategies for Improving Academic Writing Proficiency Among Kosovo Students - Kallaba, Fjolla (Yearbook of the Department of Foreign Languages and Cultures, 2024)
This study examines the perspectives of 40 lecturers from public and private universities in Kosovo on the challenges students face in developing academic writing skills and strategies for improvement. Using a structured questionnaire, lecturers identify common obstacles: insufficient foundational skills, lack of critical thinking, issues with clarity and cohesion, difficulties balancing personal ideas with sources, problems adhering to standards, and grammar and vocabulary misuse. The research highlights effective strategies to address these issues, including peer review, individualized feedback, writing workshops, critical thinking development, a supportive classroom environment, clear objectives for assignments, regular writing tasks, and offering choice in topic selection. The findings emphasize the need for comprehensive institutional support and active student engagement to enhance writing proficiency. The study offers practical recommendations to improve writing instruction, contributing to higher education quality in Kosovo.